The financial costs of delivering rural water and sanitation services in lower-income countries - Burr, Peter William (Cranfield University, 2014)
Despite the impressive progress over the last two decades in which millions of people worldwide have gained first time access to improved water and sanitation infrastructure, the reality for many is that shortly after infrastructure construction the actual service received by users slips back to unacceptably low levels. However, due to inadequate research and inconsistencies with how data and cost data has been collected and reported, very little is known of the necessary levels of expenditure required to sustain an acceptable (so called “basic”) water and sanitation service and this inhibits effective financial planning for households, communities, governments and donors alike. This thesis sought to provide a better understanding of what has historically been spent to provide different levels of water and sanitation services as a means to better understand the necessary expenditure required. Empirical findings are based on a large data sample of nearly 2,000 water points, over 4,000 latrines, and over 12,000 household surveys, which have been collected as part of three research projects (WASHCost, Triple-S, and WASHCost Sierra Leone), across five country research areas (Andhra Pradesh (India), Burkina Faso, Ghana, Mozambique, and Sierra Leone). Findings for water supply systems show that the combination of high capital investments of: $19 and $69 per person for community point sources and $33 – $216 per person for piped systems; and low recurrent expenditures of: $0.06 - $0.37 per person per year for point sources and $0.58 - $7.87 per person per year for piped systems; results in less than half of users receiving a “basic” level of service. Evidence based estimates of the required expenditure for acceptable services are found to be far greater than the “effective demand” expressed in terms of the willingness to pay of service users and national government for these services. Findings for sanitation show that constructing a household latrine that achieves “basic” service standards requires a financial investment of at least $40 that is likely to be an unaffordable barrier for many households in lower income countries. In addition the costs and affordability of periodic pit emptying remains a concern. Ultimately this research suggests that if international standard of improved water and sanitation services are to be sustained in rural areas, the international sector will likely have to provide additional investments to meet a significant proportion of the recurrent costs of delivering these services.
Keywords: Sustainability; Service Levels; Expenditure; Latrines; Maintenance; Capital Maintenance; Small Town; Financing; India; Burkina Faso; Mozambique; Ghana; Sierra Leone